The Effectiveness of Self-Compassion Training on Social and Emotional Loneliness, Perceived Personal Competence, and Tolerance of Negative Affect in Women Exposed to Domestic Violence - Mahmoudi, Fatemeh; Moradi, Shahab (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to investigate the effectiveness of self-compassion training on reducing social and emotional loneliness and increasing perceived personal competence and tolerance of negative affect among women exposed to domestic violence residing in a safe house. Methods and Materials: This study employed a quantitative quasi-experimental design using a pretest–posttest format with a control group. The statistical population consisted of women exposed to domestic violence residing in Semnan during the winter of 2025. A total of 28 participants were selected using convenience sampling and randomly assigned to experimental and control groups, with 14 participants in each group. Data were collected using the Connor–Davidson Resilience Scale, the Social and Emotional Loneliness Scale for Adults–Short Form, and the World Health Organization Domestic Violence Questionnaire. The experimental group participated in a self-compassion training program based on the protocol developed by Karakasidou and Stalikas (2017), which consisted of six weekly sessions lasting 120 minutes each, while the control group received no intervention. Data analysis was conducted using multivariate and univariate analyses of covariance in SPSS-27. Findings: The results of multivariate and univariate analyses of covariance demonstrated significant differences between the experimental and control groups in all dependent variables after controlling for pretest scores. Self-compassion training significantly reduced social loneliness (F = 29.84, p = 0.001, η² = 0.53) and emotional loneliness (F = 27.63, p = 0.001, η² = 0.51). In addition, the intervention significantly increased perceived personal competence (F = 41.92, p = 0.001, η² = 0.62) and tolerance of negative affect (F = 38.47, p = 0.001, η² = 0.59) among participants in the experimental group compared with the control group. Conclusion: The findings indicate that self-compassion training is an effective psychological intervention for reducing loneliness and strengthening resilience-related capacities among women exposed to domestic violence.